Forage intake as one estimate of the nutritive value of Flint Hills rangeland forage - J.E. Umoh; L.H. Harbers; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1977)
Forage intake was used as an estimate of the nutritive value of Flint Hills pastures. The organic matter intake (OMI) ranged from 16.3 lb. to 22.05 lb. (7.40 to 10.0 kg) between June-August, 1976, and there was no clear difference between the burned and nonburned pastures. Intake seems to fluctuate with maturity of grass, digestibility, and as grazing season progresses. More data are still needed for computing the nutritive value of Flint Hill pastures.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Forage intake; Organic matter intake